Sweet vengeance - Michaels, Fern; Alvamar, Nina (Prince Frederick, MD : Recorded Books, 2018)
Tessa Jamison couldn't have imagined anything worse than losing her beloved twin girls and husband; until she was convicted of their murder. For ten years, she has counted off the days in Florida's Correctional Center for Women, fully expecting to die behind bars. Fighting to prove her innocence holds little appeal now that her family's gone. But on one extraordinary day, her lawyers announce that Tessa's conviction has been overturned due to a technicality, and she's released on bail to await a new trial. Hounded by the press, Tessa retreats to the small tropical island owned by her late husband's pharmaceutical company. There, she begins to gather knowledge about others in similar situations to her own; people who have lost their families in horrific ways, only to see the perpetrators walk away unpunished. For the first time since her nightmare began, Tessa feels a sense of purpose. She'll use the fortune at her disposal to track down criminals who have outwitted the law.
Title from web page.
Compact discs.
Read by Nina Alvamar.
Keywords: Judicial error -- Fiction; Imprisonment -- Fiction; Murder -- Fiction; Revenge -- Fiction; Florida -- Fiction; Audiobooks